The Insects - Farb, Peter; Editors of TIME-LIFE BOOKS (Time-Life Books : Hong Kong, 1980)
The Insects provides a vibrant, visually rich introduction to the insect world for general readers. Coverage includes: Evolution and diversity of insect species across habitats Anatomy, life cycles, behavior, and ecological roles of insects Phenomena like social colonies (ants, bees), metamorphosis, and adaptations Enhanced with full-page photographs, diagrams, and engaging explanatory text.
Keywords: Insects